2021
DOI: 10.1155/2021/6664780
|View full text |Cite|
|
Sign up to set email alerts
|

Market Structure, International Competitiveness, and Price Formation of Hainan’s Fruit Exports

Abstract: Through a constant market share (CMS) model and a price index model, current research aims to analyze the impetus of the growth of Hainan, China’s fruit exports and the adverse impact of rising production costs. This paper considered the changes in the international competitiveness of Hainan’s fruit exports and analyzed the reasons for these changes. Additionally, this manuscript analyzed the effects of Hainan’s price-bargaining power on fruit exports under the condition of asymmetric information by applying a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Some scholars have analyzed grain trade using the constant market share model (CMS), pointing out that the import gravitational and structural effects are the two main elements affecting grain imports [20,21]. Along this line, Scholars have confirmed that the information available to both sides of the trade, bargaining power, the scale of import demand, the growth rate of supply, labor costs and production costs are important factors affecting the fluctuation of grain trade [22,23].…”
Section: Study On Factors Affecting Food Tradementioning
confidence: 99%
“…Some scholars have analyzed grain trade using the constant market share model (CMS), pointing out that the import gravitational and structural effects are the two main elements affecting grain imports [20,21]. Along this line, Scholars have confirmed that the information available to both sides of the trade, bargaining power, the scale of import demand, the growth rate of supply, labor costs and production costs are important factors affecting the fluctuation of grain trade [22,23].…”
Section: Study On Factors Affecting Food Tradementioning
confidence: 99%
“…Secondly, the rising costs of labor led to the gradual loss of price advantage, and the contribution of competitiveness to the growth of Hainan's fruit exports has rapidly declined [29]. e government should focus on the selection of fruit varieties, optimization of the industrial structure, and supporting policies.…”
Section: Conclusion and Further Researchmentioning
confidence: 99%
“…According to data provided by the United Nations, the Food and Agriculture Organization, and National Statistical Bureau, China is the world's largest producer of fruits, far surpassing the second-ranking country [1][2][3][4]. Simultaneously, China also leads in fruit consumption globally.…”
Section: Introductionmentioning
confidence: 99%